假设随机变量X的分布律为:[img=270x47]1802f9cda839d4f.png[/img],那么[img=57x25]1802f9cdb086003.png[/img]( )
A: 0
B: 1
C: 0.5
D: 不存在
A: 0
B: 1
C: 0.5
D: 不存在
举一反三
- 假设随机变量X的分布律为:[img=270x47]180320c1e828e98.png[/img],那么[img=57x25]180320c1f0241d3.png[/img]( ) A: 0 B: 1 C: 0.5 D: 不存在
- 假设随机变量X的分布律为:[img=270x47]180321643274560.png[/img],那么[img=57x25]180321643aee22d.png[/img]( ) A: 0 B: 1 C: 0.5 D: 不存在
- 在下列命题中:如果f(x)=[img=28x44]17e0bf9914bb2f1.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0;如果f(x)=[img=28x44]17e0bf992111a1c.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0;如果f(x)=[img=55x44]17e0bf992d8de0a.png[/img],那么[img=29x29]17e0bf9939482bb.png[/img]f(x)不存在;如果f(x)=[img=87x53]17e0bf99450fa82.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0。其中错误命题的个数是( A: 0 B: 1 C: 2 D: 3
- 设随机变量[img=93x25]180327943b4d5c6.png[/img],分布函数为F(x),密度函数为f(x),则有( ) A: P(X<0)=P(X>0) B: f(x)=f(-x) C: P(X<1)=P(X>1) D: F(x)=F(-x)
- 设随机变量[img=93x25]1803da321872708.png[/img],分布函数为F(x),密度函数为f(x),则有( ) A: P(X<0)=P(X>0) B: f(x)=f(-x) C: P(X<1)=P(X>1) D: F(x)=F(-x)